Ipsilateral synchronous papillary renal neoplasm with reverse polarity and urothelial carcinoma in a renal transplant recipient: a rare case report with molecular analysis and literature review - Daosheng Li; Fenfen Liu; Yiqian Chen; Ping Li; Yuyu Liu; Yu Pang (BMC, 2023)
Abstract Background Renal transplant recipients (RTRs) have a 3- to 5-fold higher risk of developing malignant tumors than the general population, with new malignant tumors after transplantation considered to be the leading cause of death in RTRs. In pathological practice, it is rare for neoplasms with different histology to be located in the same organ. We report the first case of a synchronous papillary renal neoplasm with reverse polarity (PRNRP) and urothelial carcinoma (UC) in the ipsilateral kidney in an RTR. Molecular detection was conducted by next-generation sequencing. Case presentation A 68-year-old female suffered from uremia 19 years ago and underwent renal transplantation (RT) after receiving dialysis for 6 months. Hematuria occurred one month ago and an enhanced CT showed that there were two abnormal density foci in the middle and lower parts of the autologous left kidney. A laparoscopic left nephrectomy and ureterectomy were performed. Gross examination revealed a mass (I) in the left renal parenchyma, 2*1.8*1.5 cm in size, that protruded from the renal capsule, and a cauliflower-like mass (II), 5*2.5*2 cm in size, adjacent to the mass (I). Microscopic findings revealed these lesions were PRNRP and UC, respectively. PCR analysis revealed a KRAS gene mutation (G12D in exon 2) in the PRNRP, while NGS analysis revealed FGFR3 (S249C in exon 7) and KDM6A (Q271Ter in exon 10 and A782Lfs in exon 17) mutations in the UC. Conclusions We report here for the first time an extraordinarily rare case of synchronous renal tumors of a PRNRP and UC in the ipsilateral kidney of an RTR. We identified simultaneous KRAS, FGFR3, and KDM6A mutations in two different renal masses in the ipsilateral kidney. Pathologic assessment with comparative molecular analysis of mutational profiles facilitates tumor studies after RT and may be of great value in clinical management strategies.